Distribution of Select Cement Proteins in the Acorn Barnacle Amphibalanus amphitrite - Schultzhaus, Janna N.; Wang, Chenyue; Patel, Shrey; Smerchansky, Madeline; Phillips, Daniel; Taitt, Chris R.; Leary, Dagmar H.; Hervey, Judson; Dickinson, Gary H.; So, Christopher R.; Scancella, Jenifer M.; Wahl, Kathryn J.; et al. (Frontiers in Marine Science, 2020)
Acorn barnacles are major marine fouling organisms. Their success is largely due to an ability to adhere to diverse substrates via a sub-micron thick proteinaceous adhesive layer that develops as the organism molts and expands its base. Recent work has expanded the set of proteins identified within the adhesive interface, but one outstanding question concerns their spatial distribution throughout the organism. Here, we employ immunological analysis of Amphibalanus amphitrite tissue sections and identify the presence of two cement proteins, AaCP19-1 and AaCP43-1, in areas far removed from the adhesive interface. Confocal imaging reveals specific staining along different tissue linings of the organism as well as other non-cementing regions. Additionally, we employ a modified, pressure cycling technology approach to recover protein from histological tissue sections to perform proteomics analysis. Mass spectrometry analysis of proteins recovered from transverse histological sections of the upper portion of barnacles indicates the presence of these same proteins, complementing the immunostaining observations. The proteomics analysis also revealed the presence of other proteins first identified in the adhesive layer. While some proteins are clearly enriched at the surface interface, our findings challenge the concept that cement proteins are exclusive to the substrate interface and suggest they may have an expanded physiological role beyond substrate adhesion-related processes of A. amphitrite.